Peran Guru dalam Pembentukan Pendidikan Karakter Bagi Perkembangan SDM di Sekolah - Bintang Ridzky Dwi Putra; Saila Rahma Annisa Nasution; Tengku Darmansah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Character education plays a crucial role in shaping a young generation with noble character, responsibility, and positive values. Teachers, as primary educators, hold a strategic role in shaping students' character in schools. This study aims to analyze the role of teachers in character education relevant to human resource (HR) development. The research employs a qualitative descriptive approach using literature review methods from various relevant journals. The findings reveal that the role of teachers is not only limited to teaching but also includes being role models, motivators, facilitators, and moral guides for students. Teachers are required to have academic competence, a personality aligned with Islamic values, and the ability to design learning strategies that support character education. Effective strategies include role modeling, giving advice, habituation, providing educational sanctions, and environmental supervision. Additionally, moral approaches such as moral modeling, moral knowing, and moral acting are implemented to instill character values. However, challenges in character development include a lack of parental support, apathy from some students and teachers, limited funding, and weak supervision in the school environment. The study also found that character education can be strengthened through collaboration between schools, committees, and parents in building routine and spontaneous activities that motivate students to exhibit positive behavior.